2024
DOI: 10.1037/tra0001233
|View full text |Cite
|
Sign up to set email alerts
|

Potentially morally injurious events as a mediator of the association of gratitude and mindfulness with distress.

Abstract: Objective: Potentially morally injurious events (PMIEs) are events that contradict one’s own personal ethics and may promote a deep sense of violation, leading to psychological distress. Individuals with greater trait gratitude and mindfulness may be less likely to perceive events as being morally injurious and may, in turn, be less likely to experience subsequent distress. The current study seeks to examine (a) PMIE rates in a multioccupational first responder sample and (b) the indirect effect of trait grati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
(51 reference statements)
1
6
0
Order By: Relevance
“…This was reflected by both frequency and mean scores for the other-MIP and betrayal-MIP subscales versus the self-MIP subscale. Notably, our sample reported relatively comparable or higher other-MIPs and betrayal-MIPS compared to those reported by veteran and first responder samples (e.g., Senger et al, 2022;Wisco et al, 2017). This is perhaps unsurprising, given the highly tumultuous time period with ever-changing policies and equipment shortages.…”
Section: Discussionsupporting
confidence: 48%
“…This was reflected by both frequency and mean scores for the other-MIP and betrayal-MIP subscales versus the self-MIP subscale. Notably, our sample reported relatively comparable or higher other-MIPs and betrayal-MIPS compared to those reported by veteran and first responder samples (e.g., Senger et al, 2022;Wisco et al, 2017). This is perhaps unsurprising, given the highly tumultuous time period with ever-changing policies and equipment shortages.…”
Section: Discussionsupporting
confidence: 48%
“…Chaplo et al. (2019) (α = .70) differed from the average for Transgression-Self, as did Senger et al (2024) (α = .63) and Ogle et al (2018) (α = .66) for Transgression-Other. Haight et al (2017) reported wider confidence intervals for Betrayal (α = .69; 95% CI [.88–.93]), indicating higher intra-sample variability, perhaps reflecting a smaller sample size ( n = 32).…”
Section: Resultsmentioning
confidence: 78%
“…The PTGI response options do not allow the rater to specify the nature of the change that has occurred for them as well as other important details such as how much change has occurred. Finally, future work should examine if these relationships still hold after accounting for known personality traits/risk factors such as neuroticism as well as investigating more prevalent mental health outcomes such as anxiety and depression (Meyer et al, 2019; Senger et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PTSD symptoms have a positive and bidirectional association with chronic pain (Brennstuhl et al, 2015). Despite these challenges, the majority of firefighters are resilient (Lee et al, 2014; Senger et al, 2022), and little research has focused on firefighter behavioral health, resilience, and well‐being. This work has great potential to inform resilience training and wellness programming in the fire service.…”
Section: Introductionmentioning
confidence: 99%